The Effect of Islamic Marketing Mix Strategy on Purchasing Decisions at Waroeng Steak and Shake in the Special Region of Yogyakarta - Rafi Evan Adi Hartawan; Muchsin Muthohar (Jurnal Economic Resource, 2023)
This study aims to identify the effect of Islamic marketing mix (7p) on purchasing decisions at Waroeng Steak and Shake in the Special Region of Yogyakarta. This study uses a non-probability purposive sampling technique in collecting sample data. Primary data collected in this study amounted to 250 respondents. Then this study used statistical analysis techniques Structural Equation Modelling (SEM) with Smar tPLS software version 3.2.9. The results of the data analysis show that several factors of the Islamic marketing mix variable (7p), namely price, people, place, promotion, and process, have a positive and significant influence on purchasing decisions. Meanwhile, products and physical evidence do not have a positive and significant influence on purchasing decisions at Waroeng Steak and Shake in the Special Region of Yogyakarta.